IMPRESSION OF LIQUIDITY, LEVERAGE, AND INDEPENDENT COMMISSIONERS ON THE VALUE OF NATIONAL PRIVATE BANK GENERAL COMPANIES - Sochib Sochib; Noviansyah Rizal (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
Management hopes to make a profit with the intention of adding value to the company. Through the provision of sufficient bank funds to meet liquidity and lending to increase profitability and increasing company value. Company value is built by managing good company assets so that profits are obtained. This information gives a signal to the stock market and is responded by the market at stock prices. This study aims to determine the influence of liquidity, leverage, and independent commissioners on firm value. The study population is national private commercial banks listed on the Indonesia Stock Exchange in the 2014-2018 period. Samples were taken based on purpose sampling so that 17 samples were obtained. The study uses a linear regression approach with liquidity variables measured by Loan to Deposit Ratio, Leverage is measured by Debt to Equity Ratio, independent commissioners are measured by the number of independent commissioners, and company value is measured by Tobin's Q. The results that liquidity has a significant negative influence on the value of the company, leverage has no influence on the value of the company, and Independent Commissioners have a significant positive influence on the value of the company.